A Levi–Civita equation on monoids, two ways - Ebanks, Bruce (Annales Mathematicae Silesianae, 2022)
We consider the Levi–Civita equation f(xy) = g1(x)h1(y) + g2(x)h2(y) for unknown functions f, g1, g2, h1, h2 : S→ℂ, where S is a monoid. This functional equation contains as special cases many familiar functional equations, including the sine and cosine addition formulas. In a previous paper we solved this equation on groups and on monoids generated by their squares under the assumption that f is central. Here we solve the equation on monoids by two different methods. The first method is elementary and works on a general monoid, assuming only that the function f is central. The second way uses representation theory and assumes that the monoid is commutative. The solutions are found (in both cases) with the help of the recently obtained solution of the sine addition formula on semigroups. We also find the continuous solutions on topological monoids.